Improving English Speaking Ability through Mobile Assisted Language Learning (Mall) Learning Model - Muhamad Sofian Hadi; Emzir Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2016)
The aims of the study to reveals in details process and result of improving English speaking ability using Mobile assisted Language Learning (MALL) learning model. This study is an action research at English Department Muhammdiyah University of Jakarta consists of 30 students as the participant. Data obtained from the result of English Speaking ability test. The results of the study showed that the learning process using Mobile Assisted Language Learning (MALL) makes the students become more active in their speech; their participation level in learning interaction shows it. The result also presented that there is significantly improvement on the students’ English speaking ability using Mobile Assisted Language Learning (MALL) from preliminary cycle to the third cycle phase in research process. The average score of the students at preliminary stage is only 42.8 then it increased in the first cycle to 53.2. While on the second cycle obtained an average score of 61.2 and increased in the third cycle to 80. So, it can be concluded that action research in improving English speaking ability using Mobile Assisted Language Learning (MALL) significantly helps the students in improving their ability to speak English.